(untitled) - Lim, Teck Ghee (Kuala Lumpur, 1977)
Contents: 1. The Malay states before 1895 ; 2. The years of uncertainty: The first decade after federation ; 3. The coming of rubber and the end of uncertainty, 1905-1912,...
Keywords: Nông nghiệp,Agriculture; Khía cạnh kinh tế,Economic aspects